Time-Resolved Radioluminescence Dosimetry Applications and the Influence of Ge Dopants In Silica Optical Fiber Scintillators - Zubair H. Tarif; Adebiyi Oresegun; Auwal Abubakar; Azmi Basaif; Hafiz M. Zin; Kan Yeep Choo; Siti A. Ibrahim; Hairul Azhar Abdul-Rashid; David A. Bradley (Quantum Beam Science, 2022)
The quality of treatment delivery as prescribed in radiotherapy is exceptionally important. One element that helps provide quality assurance is the ability to carry out time-resolved radiotherapy dose measurements. Reports on doped silica optical fibers scintillators using radioluminescence (RL) based radiotherapy dosimetry have indicated merits, especially regarding robustness, versatility, wide dynamic range, and high spatial resolution. Topping the list is the ability to provide time-resolved measurements, alluding to pulse-by-pulse dosimetry. For effective time-resolved dose measurements, high temporal resolution is enabled by high-speed electronics and scintillator material offering sufficiently fast rise and decay time. In the present work, we examine the influence of Ge doping on the RL response of Ge-doped silica optical fiber scintillators. We particularly look at the size of the Ge-doped core relative to the fiber diameter, and its associated effects as it is adjusted from single-mode fiber geometry to a large core-to-cladding ratio structure. The primary objective is to produce a structure that facilitates short decay times with a sufficiently large yield for time-resolved dosimetry. RL characterization was carried out using a high-energy clinical X-ray beam (6 MV), delivered by an Elekta Synergy linear accelerator located at the Advanced Medical and Dental Institute, Universiti Sains Malaysia (USM). The Ge-doped silica optical fiber scintillator samples, fabricated using chemical vapor deposition methods, comprised of large core and small core optical fiber scintillators with high and low core-to-cladding ratios, respectively. Accordingly, these samples having different Ge-dopant contents offer distinct numbers of defects in the amorphous silica network. Responses were recorded for six dose-rates (between 35 MU/min and 590 MU/min), using a photomultiplier tube setup with the photon-counting circuit capable of gating time as small as 1 μs. The samples showed linear RL response, with differing memory and afterglow effects depending on its geometry. Samples with a large core-to-cladding ratio showed a relatively short decay time (<1 ms). The results suggest a contribution of Ge-doping in affecting the triplet states of the SiO2 matrix, thereby reducing phosphorescence effects. This is a desirable feature of scintillating glass materials that enables avoiding the pulse pile-up effect, especially in high dose-rate applications. These results demonstrate the potential of Ge-doped optical-fiber scintillators, with a large core-to-cladding ratio for use in time-resolved radiation dosimetry.